The ethical and legal dilemmas of Telepsychiatry - Chatzi, Maria (Bioethica, 2024)
This paper was written in the framework of my internship at the National Commission for Bioethics and Technoethics of the Hellenic Republic. It constitutes an attempt at exploring the ethical and legal dilemmas of the medical practice of telepsychiatry. Telepsychiatry, as well as other forms of telemedicine, has become a prevalent way through which patients gain access to healthcare and with many research papers reporting on its effectiveness and advantages, telepsychiatry has gained a lot of proponents in the scientific and healthcare community. However, several questions regarding the ethical and legal nature of the practice remain unanswered and this can put patients and other users of telemental health services under risk for basic rights violations. In this paper, at first the scientific data supporting the use of telepsychiatry will be cited. In addition to that, there will be discussion of several ethical dilemmas that have been reported concerning the use of telemedicine in psychiatry during the past few years and there will be reference to the medical code of ethics. Following that, there will be reference to the existing legislation for telepsychiatry in Greece and the legal issues that can arise will be analyzed. In spite of the fact that the advantages and ethical pitfalls of telepsychiatry are common in many countries, the focus of this paper will be on Greece’s code of medical ethics and legislation due to the lack of relevant bibliography on the matter, even though telepsychiatry is widely used by Greek patients. Finally some suggestions will be made on what ought to be ameliorated in regards to the current conditions, so as to make sure telepsychiatry is in line with the basic principles of bioethics.